Marine actinobacteria showing phosphate-solubilizing efficiency in Chorao Island, Goa, India - Dastager, Syed Gulam; Damare, Samir (Current Microbiology, 2013)
The occurrence and distribution of an actinobacteria group of bacteria capable of dissolving insoluble phosphates were investigated in this study in marine environments, especially in sediments of Chorao Island, Goa Province, India. A total of 200 bacterial isolates of actinobacteria was isolated. All isolates were screened for phosphate-solubilizing activity on Pikovskaya's agar. Thirteen different isolates exhibiting maximum formation of halos (zone of solubilization) around the bacterial colonies were selected for quantitative estimations of P-solubilization. Quantitative estimations for P-solubilization were analyzed for up to 10 days at intervals of 24 h. Maximum solubilization from 89.3 +/- A 3.1 to 164.1 +/- A 4.1 mu g ml(-1) was observed after 6 days of incubation in six of all isolates, while the isolate NII-1020 showed maximum P-solubilization. The increase in solubilization coincided with the drop in pH. Many of these species showed wide range of tolerance to temperature, pH, and salt concentrations. Further, 16S rRNA gene sequence analyses were carried to identify the bacterial groups which are actively solubilized phosphate in vitro. Gene sequencing results reveal that all isolates were clustered into six different actinobacterial genera: Streptomyces, Microbacterium, Angustibacter, Kocuria, Isoptericola, and Agromyces. The presence of phosphate-solubilizing microorganisms and their ability to solubilize phosphate were indicative of the important role played by bacteria in the biogeochemical cycle of phosphorus and the plant growth in coastal ecosystems.